(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article reveals the essence and content of project technology, the views of specialists on the stages of its development in educational practice, its advantages and disadvantages. Foreign experience of using project methodology in universities in the modern educational context is analyzed. It is shown that the successful implementation of project-based learning in the work of higher education is associated with the modernization of the structure and content of the educational process and overcoming existing stereotypes of university education.